Proses pemecahan masalah operasi aljabar oleh siswa SMP berdasarkan tahapan IDEAL ditinjau dari kemampuan matematika - Ardiani Rahma Putri; Danang Setyadi; Helti Lygia Mampouw (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This research aims to describe the problem solving process of algebraic operations by junior high school students is based on IDEAL stages in terms of mathematical abilities. The type of this research is descriptive qualitative. The main instrument in this study is the researchers themselves, assisted problem solving test and interview guides. Data analyzed is problem solving procces based on the five IDEAL stages, namely identify problem, define the problem, explore alternative approaches, acting on a plan, and looking the effects. The selected subject is three students in grade VIII in SMP N 1 Salatiga. The result showed that in subjects with high mathematical abilities capable to finish these five stages, subjects with moderate mathematical abilities are only able to finish the five stages in open questions type 1 and can not finish the stages of reviewing open questions type 2 and closed questions. In subjects with low mathematical abilities only finish the four stages in open questions type 1 and closed questions, and three stages in open questions 2.